2006
DOI: 10.1002/jat.1122
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of neutropenia on carbon tetrachloride-induced hepatotoxicity in rats

Abstract: The preventive effect of neutropenia on carbon tetrachloride (CCl4)-induced hepatotoxicity was examined in rats. In rats treated once with CCl4 (1 ml kg(-1), i.p.), the serum levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST), indices of liver cell damage, and the hepatic activity of myeloperoxidase (MPO), an index of tissue neutrophil infiltration, increased at 6 h after the intoxication and further increased at 24 h. The liver of CCl4 -treated rats showed an increase in the concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 61 publications
(100 reference statements)
7
21
0
Order By: Relevance
“…CCl 4 exposure generates excessive levels of nitric oxide (NO) through activation of iNOS, thus contributing to damage in hepatic tissue [20]. Hepatic injury in rats treated with CCl 4 also developed with an increase in the activity of MPO, an index of hepatic neutrophil infiltration [21]. Our results revealed that STM significantly inhibited MPO and iNOS activity consistent with decreased NO level.…”
Section: Discussionsupporting
confidence: 50%
“…CCl 4 exposure generates excessive levels of nitric oxide (NO) through activation of iNOS, thus contributing to damage in hepatic tissue [20]. Hepatic injury in rats treated with CCl 4 also developed with an increase in the activity of MPO, an index of hepatic neutrophil infiltration [21]. Our results revealed that STM significantly inhibited MPO and iNOS activity consistent with decreased NO level.…”
Section: Discussionsupporting
confidence: 50%
“…Also the concentration of TBARS, as a marker for lipid peroxidation, was lower in the livers of the neutrophil depleted rats. These findings showed that oxidative liver damage was, at least partly, mediated by neutrophils [90]. The impact of IL-6 trans-signaling in neutrophil depleted animals after CCl 4 liver damage still needs to be examined.…”
Section: Impact Of Il-6 Signaling In Drug-induced Hepatoxicitymentioning
confidence: 92%
“…However, overexuberant or prolonged neutrophil infiltration can exacerbate tissue injury, leading to disease. Within the liver, inappropriate inflammation in response to sterile tissue injury contributes to the pathogenesis of many noninfectious diseases, including drug-or toxin-induced liver injury, ischemia-reperfusion injury, autoimmunity, alcoholic steatohepatitis, and others (Bautista 1997;Bonder et al 2004;Jaeschke and Farhood 1991;Jaeschke, Farhood, and Smith 1990;Liu et al 2006;Ohta et al 2006). Although sterile inflammation is a well-known phenomenon, the mechanisms that initiate and regulate the innate immune response to cell death have only recently begun to unfold (Chen and Nuñez 2010;Kono and Rock 2008).…”
Section: Neutrophils and Intravascular Immunity In The Liver During Smentioning
confidence: 99%
“…As such, overexuberant neutrophil recruitment and indiscriminant release of toxic mediators contribute fundamentally to the pathogenesis of many diseases. In particular, many acute and chronic pathologies of the liver are mediated and/or exacerbated by neutrophilic inflammation, such as sepsis and endotoxemia (Jaeschke et al 1996;Molnar et al 1997) and ischemia-reperfusion injury (Jaeschke and Farhood 1991;Jaeschke, Farhood, and Smith 1990;Martinez-Mier et al 2001), as well as alcoholic (Bautista 1997), viral (Takai et al 2005), autoimmune (Bonder et al 2004), and toxin-or drug-induced hepatitis Ohta et al 2006). Despite the central role of neutrophils in a variety of liver diseases, the molecular mechanisms that allow these cells to home to the liver, and their functions therein, are not well understood.…”
Section: Introductionmentioning
confidence: 99%